Violence within mental health services: how to enhance risk management - O'Rourke M; Wrigley C; Hammond S (Dove Medical Press, 2018)
Margaret O’Rourke,1 Conal Wrigley,2 Sean Hammond3 1School of Medicine, University College Cork, Cork, Ireland; 2INFANT Research Group University College Cork, Cork, Ireland; 3School of Applied Psychology, University College Cork, Cork, Ireland Abstract: This paper aims to present best practice in risk management within mental health services. Its purpose is to explore the prevalence of violence within mental health services, to examine the nature of risk, highlight lessons learned and guidance published on safer services, and to identify ways to enhance risk management in mental health care. We reflect on current health care practices in the UK, England and Wales, and Ireland and refer to research and practice from other jurisdictions internationally where it exists. Keywords: violence, mental health, risk management, best practice